Spatial computing an AI-driven business revolution - Hackl, Cathy; Cronin, Irena (Ascent Audio, 2024)
Written by Irena Cronin, renowned consultant in the immersive space, and Cathy Hackl, globally recognized tech and gaming executive, futurist, and speaker, Spatial Computing: An AI-Driven Business Revolution reveals exclusive insider knowledge of what's happening today in the convergence of AI and spatial computing. Spatial Computing is an evolving 3D-centric form of computing that uses AI, Computer Vision, and extended reality to blend virtual experiences into the physical world, breaking free from screens into everything you can see, experience, and know.
Online resource; title from title details screen (O'Reilly, viewed December 10, 2024)
Keywords: Business enterprises -- Technological innovations; Artificial intelligence; Computer vision; Entreprises; Innovations; Intelligence artificielle; Vision par ordinateur; artificial intelligence; Audiobooks; Livres audio